An investigation of the citation transformation types in M.A. and PhD theses - Fatma Şeyma Doğan; Oktay Yağız; Işıl Günseli Kaçar (International Journal for Educational Integrity, 2018)
Abstract This study investigates the types of citation transformation preferred by both English L1 (native language) writers and Turkish writers who use English as a foreign language (L2). The corpus consists of 34 theses, 17 of which are Turkish writers’ theses in English language including 10 M.A. and 7 PhD theses and 17 English L1 writers’ theses comprised of 10 M.A. and 7 PhD theses. Based on the relevant literature, a rubric was prepared by the researchers in order to analyse the theses by means of qualitative content analysis. The findings revealed that three forms of content integration consisting of direct quotation, patchwriting and critical evaluation were markedly different in English L1 and Turkish writers’ theses. Turkish L1 writers’ overuse of direct quotation and patchwriting attracted attention compared to English L1 writers.